INTEGRATED DEVELOPMENT OF MALAY ETHNOMATHEMATICS: DESIGNING STUDENT WORKSHEETS ON ADDITION AND SUBTRACTION OF INTEGERS - Ramadhani, Tasya Manty; Putra, Zetra Hainul; Fendrik, Muhammad; Ahmad, Sagheer (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The use of unengaging and decontextualized worksheets has been identified as a significant barrier to the effective learning of mathematical concepts in elementary schools, leading to diminished student interests and understanding. This study aims to address this issue by developing interactive student worksheets grounded in Malay ethnomathematics, specifically tailored for teaching addition and subtraction to second-grade elementary students. An ethnographic approach was adopted to integrate ethnomathematical concepts with local cultural contexts, thereby enhancing the relevance and engagement of the learning experience. The research employed a Research and Development (R&D) methodology, utilizing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) as the framework for development. Data collection was collected through interviews, observations, and questionnaires, with a sample size of sixteen students. The findings of the study revealed the following: (1) The quality of the developed student worksheets was categorized as valid, based on evaluations by three validators specializing in language, content, and media. The validation scores were 93% for language, 93% for content, and 100% for media. (2) The practicality of the worksheets was assessed by both teachers and students, with teachers rating the practicality at 82% and students at 81%. In conclusion, the developed student worksheets were found to be both valid and practical, making them suitable for implementation in elementary school settings. This study underscores the potential of culturally contextualized educational materials to enhance students’ engagement and understanding in mathematics.